Infant gut bacterial community composition and food‐related manifestation of atopy in early childhood. Issue 1 (5th December 2021) - Joseph, Christine LM; Sitarik, Alexandra R.; Kim, Haejin; Huffnagle, Gary; Fujimura, Kei; Yong, Germaine Jia Min; Levin, Albert M.; Zoratti, Edward; Lynch, Susan; Ownby, Dennis R.; Lukacs, Nicholas W.; Davidson, Brent; et al.
Abstract: Background: Immunoglobulin E–mediated food allergy (IgE‐FA) has emerged as a global public health concern. Immune dysregulation is an underlying mechanism for IgE‐FA, caused by "dysbiosis" of the early intestinal microbiota. We investigated the association between infant gut bacterial composition and food‐related atopy at age 3–5 years using a well‐characterized birth cohort. Methods: The study definition of IgE‐FA to egg, milk, or peanut was based on physician panel retrospective review of clinical and questionnaire data collected from birth through age 3–5 years. Using 16S rRNA sequencing, we profiled the bacterial gut microbiota present in stool specimens collected at 1 and 6 months of age. Results: Of 447 infants with data for analysis, 44 (9.8%) met physician panel review criteria for IgE‐FA to ≥1 of the three allergens. Among children classified as IgE‐FA at 3–5 years, infant stool samples showed significantly less diversity of the gut microbiota compared with the samples of children classified as no IgE‐FA at age 3–5 years, especially for milk and peanut (all covariate‐adjusted p 's for alpha metrics <.007). Testing of individual operational taxonomic units (OTUs) revealed 6‐month deficiencies in 31 OTUs for IgE‐FA compared with no IgE‐FA, mostly in the orders Lactobacillales, Bacteroidales, and Clostridiales . Conclusions: Variations in gut microbial composition in infant stool were associated with a study definition of IgE‐FA at 3–5 years of age. This included evidence of a lack of bacterial diversity, deficiencies in specific OTUs, and delayed microbial maturation. Results support dysbiosis in IgE‐FA pathogenesis.